Ageing simulation of a hydraulic engine mount: A data-informed finite element approach. (September 2019) - Soltani, Payam; Pinna, Christophe; Wagg, David J; Whear, Roly
Hydraulic engine mounts are key elements in an automotive vehicle suspension system that typically experience a change of their designed function during their working lifetime due to progressive material ageing, primarily from the elastomeric component. Ageing of the engine mount, resulting from severe and continuous mechanical and thermal loads, can have a detrimental impact on the ride and comfort and long-term customer satisfaction. This paper introduces a new practical methodology for simulating the ageing behaviour of engine mounts resulting from the change in properties of their elastomeric main spring component. To achieve this, a set of dynamic mechanical thermal analysis tests were conducted on elastomeric coupons taken from a set of engine mounts with different service and ageing conditions. These experimental results were used to characterise the change in mechanical response of the elastomer and to build up an empirical elastomer ageing model. Then a finite element model of the main spring was developed that used the elastomer ageing model so that the ageing behaviour of the engine mount could be simulated. The resulting ageing model was verified by using experimental results from a second batch of ex-service engine mounts. The results show an increasing trend of the vertical static stiffness of the engine mounts with distance travelled (or age) up to a certain distance (approximately 95, 000 km). The trend is then reversed and a softening effect is observed. Moreover, the results reveal that both the maximum stiffness value and the distance travelled at the peak stiffness decrease as the temperature increases.